“Disregarded Professionals”: Social Workers and Their Power - Švedaitė-Sakalauskė, Birutė; Gvaldaitė, Lijana; Buzaitytė-Kašalynienė, Jolita (Socialinė teorija, empirija, politika ir praktika, 2014)
SummaryPhenomenon of social workers as “disregarded professionals” is presented in the article. The phenomenon is empirical category which has been reconstructed during qualitative research. Methodology of grounded theory has been used to reveal causal, contextual and intervening conditions of the phenomenon. Still the focus of the article is on the actualised and non-actualised strategies of coping with phenomenon of “disregarded professionals” and consequences of those strategies for social work practice. The phenomenon is experienced by social workers when they are faced with unjustified, inadequate, ungrounded requirements which don’t correspond with the essence of the professional activity. It has been revealed that the strategies of coping with phenomenon of “disregarded profession” are equally determined by the personality of a social worker and the specific contextual conditions, in which the social worker is working. Organisations which create supportive and encouraging professional development environment are opening possibilities for different quality strategies of coping with the phenomenon to compare with non-supportive, non-encouraging and even disruptive professional development organisations / environments.